2006
DOI: 10.1016/j.pcrj.2006.01.004
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of smoking in Northern Greece

Abstract: SummaryAim: To investigate the prevalence of smoking in the general population and in specific population sub-groups in Northern Greece. Methods: A cross-sectional study was conducted during the period 1999-2001 on a 5% sample (23,840) of those people aged between 21 to 80 out of a total general population of 653,249. 21,854/23,840 general population subjects were interviewed. In addition, we interviewed 9,276 high school students, 1,072 medical students, 597 medical doctors within the National Health System, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 9 publications
2
16
2
3
Order By: Relevance
“…It has recently been shown that 96% of women above the age of 60 in northern Greece were non-smokers. 41 Additionally, it is likely that more smokers and especially those with respiratory symptoms may have attended the spirometry program, and this may further account for the lower number of female participants in our study.…”
Section: Discussionmentioning
confidence: 92%
“…It has recently been shown that 96% of women above the age of 60 in northern Greece were non-smokers. 41 Additionally, it is likely that more smokers and especially those with respiratory symptoms may have attended the spirometry program, and this may further account for the lower number of female participants in our study.…”
Section: Discussionmentioning
confidence: 92%
“…In Saudi Arabia, Pakistan, Egypt, and southern India, 11-14% of medical students were reported as regular smokers (Abolfotouh et al 1998;Mostafa & Shokeir 2002;Khan et al 2005;Al-Turki 2006;Mohan et al 2006). In Europe the situation may be worse, with 41% of Greek, 22% Italian, 21-32% Polish, 18% Spanish, and 15% German medical students smoking (Mas et al 2004;Kowalska et al 2006;Rea & Tortorano 2006;Sichletidis et al 2006;Sieminska et al 2006).…”
Section: Comparisons -Curricula For Specific Lifestyle Determinantsmentioning
confidence: 99%
“…A review article published in 2007 pointed out seven population-based epidemiological studies in the time period 2000-2006 regarding the smoking habits of high-school and university students [8]. According to these studies, smoking prevalence among high-school students ranged from 10% to 32% for 15-year-old to a maximum of 50% for 16-to 19-year-old students [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%